(untitled) (Książnica Śląska, 2025)
The author presents one of the most valuable manuscripts of the Biblioteka Śląska w Katowicach – the 19th-century Album autografów, once belonging to the secretary of the Koło Literacko-Artystyczne in Lwów, Witold Bartoszewski. The Album contains autographs of writers, artists, politicians and scholars, e.g. Jan Kasprowicz, Maria Konopnicka, Adam Asnyk and Michał Bałucki. The text introduces the owner of the Album and explains the circumstances of the creation of individual entries.